Histological Effect of Onion, Tea Against Lead Acetate in Some Organs of Sprague–Dawley Rats - Ammar Abdulhasan Aldhalemi; Ali Joodi shuna Al-Fatlawi; Zinah Talib Alsallami; Ashraf Raoof Mohammed Ali; Murtadha Abdulhasan Aldhalemi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study aimed to investigate the negative effects of lead acetate on the liver and kidneys tissues of maleSprague Dawley rats. It was conducted on 28 male rats of the aforementioned strain. The rats were dividedinto four groups, including the control group (provided with regular fodd only), lead acetate group (LD 50),onion group (provided with lead with water and dried onion powder at a rate of 4% with the fodd) and teagroup (provided with lead with water and tea powder at 1% with the fodd). The results of the current studyshowed that the control group was a normal marker of hepatocytes (Central Vein, Sinosoid, Hepatocyte)While we note that the results of the T2 group, we find that there is severe damage to the tissues of theliver cells. Through the results of the study, we find the occurrence of a large grouping of lymphocytes andsevere congestion. Hepatocytes, the results of the T4 group showed hemorrhage and no accumulation oflymphocytes, as was the case in the results of the T2 group. Regarding the sections of renal tissue, the resultsof the study showed that the control group had normal tissues as well as parts of the kidneys (BowmansCapsule, glomerulus, Distal, convoluted tubule, Proximal convoluted tubules), while the renal tissue for T2suffered from severe hemorrhage and very severe cell damage, and compared with the results of T3, we findthat the renal tissue of T3 is distinguished by the presence of partially shrink glomerular and is not betterthan both T2 and T4 tissues, which are characterized by a clear shrinkage of the glomeruli and the presenceof hemorrhage, but with less than T3. Therefore, we find that the best results in terms of therapeutic nutritionfor liver cells are T4 (tea 1%) and kidney T3 cells (onion 4%).